Detection of Antibiotic and Disinfectant Resistant Genes in E. coli Isolated from Broilers Chickens - Enany, Mohamed E.; Eid, Samah; Mohamed, Basma A.; Al-Atfeehy, Nayera M. (Journal of Advanced Veterinary Research, 2023)
Avian colibacillosis is one of the most serious diseases that affect poultry and causes substantial morbidity and mortality rates as well as high economic losses. E. coli, are capable of acquiring resistance genes via gene transfer. The development of extended spectrum lactamases, or broad-spectrum lactamases, in E. coli is the most serious resistance mechanism. The goal of the current study was to detect the resistance associated genes of multi drug resistant E. coli isolated from broiler chicken by using PCR technique. In the current study PCR applied on 10 multidrug resistant E. coli isolates for detecting Î²-lactamases resistance genes (blaTEM, blaSHV), integron resistance gene (Int1, Int3), PCR was also used to detect disinfectant resistance genes as Quaternary ammonium compounds resistance genes (QacCD, QacA/B and QacED1). PCR results for antibiotic resistance associated gene showed that (10/10) of tested isolates had blaTEM and int1(10/10), blaSHV (6/10) and int3 (2/10) also PCR results for disinfectant resistance associated genes showed that (8/10) of E. coli isolates had QacED1, QacCD (2/10), and QacA/B (2/10). The (10) broilers flocks investigated in the study were infected with multi drug resistant, strains of E. coli, that haboured Î²-lactamases, integron resistance associated gene and quaternary ammonium compounds resistance genes.